1997
DOI: 10.1038/bjc.1997.431
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between prognostic score and thyrotropin receptor (TSH-R) in papillary thyroid carcinoma: immunohistochemical detection of TSH-R

Abstract: Summary We have demonstrated the expression of thyrotropin receptor (TSH-R) in thyroid neoplasms (13 adenomas, 21 papillary carcinomas, two follicular carcinomas) and adjacent normal thyroid using the monoclonal antibody against human TSH-R and have also demonstrated a relationship between prognostic scores and the expression of TSH-R. Among the adenomas, eight showed an intensity similar to that of normal thyroid and five showed a higher intensity than normal. Two tumours exhibited heterogeneous distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
4
14
1
3
Order By: Relevance
“…Futhermore, in agreement with another previous finding (6), we demonstrated that the poorlydifferentiated components, such as trabecular, solid and insular ones, had decreased TSHR expression in most of the PDC cases. A previous study reported that clinically high-risk patients with PTC tended to show weaker TSHR staining than that of normal thyroid of the same patients (16). However, in the present study we found that the PTC cases did not show weaker staining than the PDC cases, which may indicate that the decline of TSHR expression affects the biological behavior of thyroid carcinomas.…”
Section: ------------------------------------------------------------contrasting
confidence: 57%
See 1 more Smart Citation
“…Futhermore, in agreement with another previous finding (6), we demonstrated that the poorlydifferentiated components, such as trabecular, solid and insular ones, had decreased TSHR expression in most of the PDC cases. A previous study reported that clinically high-risk patients with PTC tended to show weaker TSHR staining than that of normal thyroid of the same patients (16). However, in the present study we found that the PTC cases did not show weaker staining than the PDC cases, which may indicate that the decline of TSHR expression affects the biological behavior of thyroid carcinomas.…”
Section: ------------------------------------------------------------contrasting
confidence: 57%
“…Certain authors have reported TSHR localized along the basal surface (14), while others reported it in the cytoplasm (16). Although we examined another antibody used in the previous reports (6,14,16), there is no remarkable difference between these two antibodies. To confirm the antibody specificity, Western blotting was performed using normal thyroid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Ao contrário, no trabalho feito por Tanaka e cols. (24), observou-se que a expressão de TSHR2 seria menor nas variantes de pior prognóstico, porém, deixando claro que essa menor expressão seria concluída levando-se em conta a coloração heterogênea de diferentes áreas dentro do tumor, fato este não levado em consideração neste estudo.…”
Section: Variantes De Prognóstico Intermediáriounclassified
“…Há relação inversa entre o nível de receptor de TSH e a agressividade de carcinomas de tiróide (23). Os carcinomas papilíferos com baixa expressão de receptor de TSH possuem tendência para serem encontrados em estágios avança-dos e estão associados com pior prognóstico (24).…”
unclassified
“…Tanaka and coworkers (Tanaka et al 1997) studied TSHR protein expression in 21 PTCs (18 well differentiated) and 2 FTCs (both well differentiated) using IHC. They compared receptor immunostaining intensity and distribution to surrounding thyroid tissue.…”
Section: :6mentioning
confidence: 99%